Satria Mandala Museum as a Historical Heritage of the Nation's Struggle to Increase the Sense of Nationalism of the Younger Generation - Kusumah, Yudha (Dinasti International Journal of Digital Business Management, 2025)
The concept of museums according to new museology is to be relevant and useful for education and involve community participation. The problem of this research is how museum management efforts are based on the new museum concept. The purpose of this research is that the Satria Mandala Museum can be in line with the novelty or in accordance with the current conditions to serve and meet the needs of the community according to the new museum concept, hopefully. The research method used in this research is qualitative by using the concept of a new museum and applying the concept of mutation theme. Data collection is done by using primary data and secondary data. From the results of the research, it can be seen that the Satria Mandala Museum currently needs to make management efforts based on the New Museum concept, which is oriented towards education and the role of the community.